Meningkatkan Mutu Produk Plastik Dengan Metode Taguchi - Hartono, Moh. (Jurnal Teknik Industri, 2012)
Plastic waste is one type of waste that can not be broken down into the organic waste. Utilization of waste plastics to beÂ recycled into plastic with better quality are rarely implemented. This study aims to utilize plastic waste in order to improve the quality of plastic products by Taguchi experimental design method that combines the pure plastic material composition of ore and recycled plastic (type PP/Polypropilena) with a certain pressure and temperature to produce a tensile strength of the plastic the better. From the experimental results, btained by a combination of material composition of 30% recycled plastic, the pressure of 6.5 atm and a temperature of 180 Â°C. The composition obtained by the average tensile strength of 991.667 Newton, and Signal to Noise ratio (Larger is better) by 59, 9255. Statistically, tur ulang he combination was significantly affected by alpha at 0:05 Taguchi method through experiments with a matrix orthogonal array L8 (23).